Kontrol' techniceskoj podgotovlennosti v pryžkovych vidach desjatibor'ja - Ogandzhanov, A. L.; Moshkin, I. I.; Kosikhin, V. P. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
This study is devoted to the formation of the methodology for the current control of technical readiness in decathlon. A technique for monitoring the technical skills of all-athletes in all-round jumping in decathlon has been developed and tested in the practice of current and competitive examinations. The control results in combination with the developed model characteristics allow, based on the development of model kinematic characteristics of high, long and pole vaults, to highlight the lagging and strengths of the athlete`s technical preparedness, and on this basis to adjust his technical training.